2012
DOI: 10.1016/j.jvs.2012.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Screening by Noninvasive Imaging for Cardiovascular Prevention: A Systematic Review

Abstract: Conclusion: Patients with Marfan syndrome who have ascending aorta diameters of Ͻ50 mm have a low risk of sudden death or aortic dissection. Fifty millimeters is a reasonable threshold for prophylactic aortic surgery in patients with Marfan syndrome. Summary: During the last 30 years, the life expectancy for patients with Marfan syndrome has increased by 30 years (Pyeritz RE, et al, Heart 2009;95:173-5). Improvement of survival in patients with Marfan syndrome is likely multifactorial but includes more widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Atherosclerosis is the main pathology for cardiovascular and cerebrovascular diseases, and it progresses with chronic inflammation (31)(32)(33). TPL is a compound originally extracted from the plant T. wilfordii Hook.f., which has potent anti-inflammatory activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the main pathology for cardiovascular and cerebrovascular diseases, and it progresses with chronic inflammation (31)(32)(33). TPL is a compound originally extracted from the plant T. wilfordii Hook.f., which has potent anti-inflammatory activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…There is great interest (and value) in providing people with vascular imaging results of the coronary and carotid arteries to prompt healthful behaviour change and better management of CVD 7,40 . However, the provision of the imaging results may produce markedly different emotions-and as a result, downstream behaviours-depending upon the way in which they are received and appraised.…”
Section: Study Rationale and Guiding Questionmentioning
confidence: 99%
“…Scoping reviews aim to map key concepts, main sources and types of evidence available in a research area and can be undertaken where an area is complex or has not been comprehensively reviewed before 38 . Previous reviews reported very little evidence relating to QOL or mental distress following provision of vascular imaging results to asymptomatic adults 7,[39][40][41][42] . It is important, therefore, to collate evidence relating to the findings available in this field, how studies in this field have been conducted, the key characteristics of studies, and important knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Showing subjects their CCS is strongly associated with subjects initiating therapy (28) and in a systematic review of eight non-randomised studies (n=2,994) evaluating the use of CCS in improving adherence to therapy, Rodondi et al (29) found that subjects with evidence of atherosclerosis showed better perception of cardiovascular risk and improved adherence to lifestyle advice. However, in four RCTs (n=709), screening did not influence risk for poorer outcomes, with the exception, in one study, of improved smoking cessation (18% vs. 6%, p=0.03).…”
Section: Accepted Manuscriptmentioning
confidence: 99%